PERBANDINGAN EFISIENSI WAKTU PROSES PENGAKSESAN DATA ANTARA QUERY BERBENTUK JOIN DENGAN SUBSELECT - Raden Bagus Bambang Sumantri; Guntur Subari; Fajar Mahardika; Hadi Jayusman (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Queries in a database application system, have a great influence on the success of application development. Frequently used query forms include subselect and join. Choosing the right query form will affect the performance of the database application. Database applications are sometimes slow to respond because of slowness in their databases. The selection of the form of the query to be used is the first step of forming a query, because the resulting query will affect access from the database. The purpose of this study is to determine the form of SQL with a faster data access time, whether join or subselect. The subject of this study is queries made in the form of joins and subselects. The methods that will be used in this study are literature and experimental methods. The result of this study is a comparison table of access time between join and subselect queries. From the results of the query comparison, it can be concluded that the join form query is a faster SQL form compared to subselect. A faster query is determined from testing done by creating a simple application using both forms of the query.